2019
DOI: 10.3390/min9040237
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Phosphate Mine Waste Rocks as Materials for Road Construction

Abstract: The road construction sector is a worldwide high consumer of natural aggregates. The use of unusual industrial by-products in road techniques can contribute to the conservation of non-renewable natural resources and the reduction of wastes produced by some industries. Phosphate waste rocks could be considered as potential alternative secondary raw materials in road construction. The use and valorization of these wastes is currently limited according to the Moroccan guide for road earthworks (GMTR). The guide h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…LA ˃ 53%) and wear (i.e. MD ˃ 53%) resistance (Amrani et al 2019). In the same study, fragmentation resistance increased for a fraction of these rocks with small content of cristobalite and illite, and high quartz content with LA ˂ 48% (Amrani et al 2019).…”
Section: Dominance Of Primary Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…LA ˃ 53%) and wear (i.e. MD ˃ 53%) resistance (Amrani et al 2019). In the same study, fragmentation resistance increased for a fraction of these rocks with small content of cristobalite and illite, and high quartz content with LA ˂ 48% (Amrani et al 2019).…”
Section: Dominance Of Primary Mineralsmentioning
confidence: 99%
“…MD ˃ 53%) resistance (Amrani et al 2019). In the same study, fragmentation resistance increased for a fraction of these rocks with small content of cristobalite and illite, and high quartz content with LA ˂ 48% (Amrani et al 2019). The authors, however, suggested that the variation of performance was due to the presence of clay and flintstone.…”
Section: Dominance Of Primary Mineralsmentioning
confidence: 99%
“…Cementitious materials, including geopolymers and ecological cement, were developed using phosphate mining by-products [34,35]. Through an experimental study, Amrani et al [36] investigated the possibility of phosphate wastes disposal in the road construction field. The results of this study confirmed that the obtained physical, geotechnical, chemical, mineralogical and environmental properties of wastes satisfy the conventional characteristics to be used as materials for embankments.…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight aggregates that are composed of PHWWC, cement kiln and clay were studied by [9]. Amrani et al [10] found that phosphate wastes could be successfully used as natural aggregates similar to conventional materials frequently used in road infrastructure. The study of Shen et al [11] provided a quantitative analysis indicating the safe use of these wastes in building.…”
Section: Introductionmentioning
confidence: 99%